Działanie Momentu Skupionego na Tarcze Kształtu Półpłaszczyzny - Szelągowski, F. (Engineering Transactions, 1959)
Equations are derived for the determination of stresses any point of a semi-infinite stresses Xy, Xx, Y, at plate subjected to the action of a concentrated moment.